The nonlinear observer-based fault diagnosis method for the high altitude airship - Jichen Hu; Ming Zhu; Tian Chen (Electronic Research Archive)
We investigated an observer-based fault diagnosis method for the high altitude airship (HAA). The nonlinear kinematics and dynamics model, which considers model uncertainties and external disturbances, were obtained. The nonliear portion of the model was re-expressed to the linear parameter varying frame mathematically with an auxiliary design. Subsequently, in order to realize fault detection, isolation, and reconstruction, diverse types of robust were observers designed, respectively. Furthermore, all these mentioned observers were achieved via the linear matrix inequation framework. The effectiveness of the proposed method was verified by different fault cases in an HAA simulation system.